2022
DOI: 10.1186/s12884-022-05028-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of fetal facial profile markers during the first trimester

Abstract: Objectives To study the correlations between facial profile markers and crown-lump length (CRL) in a Chinese population, and to evaluate the clinical value of these markers for abnormal fetuses during the first trimester (11 to 13+6 gestational weeks).  Methods The facial profile markers were as followings: inferior facial angle (IFA), maxilla-nasion-mandible (MNM) angle, facial maxillary angle (FMA), frontal space (FS) distance and profile line (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
2
2
0
Order By: Relevance
“…At present, studies on these facial markers mainly focus on the second and third trimester, we previously demonstrated the feasibility of measuring these markers during the first trimester, with excellent intra- and inter-operator consistency [ 18 ]. We further concluded that these markers have certain diagnostic value for fetal abnormalities [ 24 ]: IFA had a certain value in the diagnosis for trisomy 21 and trisomy 18; FMA had the excellent accuracy in detecting trisomy 18; MNM angle and FS distance were reliable indicators for screening CLP, which was consistent with this study.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…At present, studies on these facial markers mainly focus on the second and third trimester, we previously demonstrated the feasibility of measuring these markers during the first trimester, with excellent intra- and inter-operator consistency [ 18 ]. We further concluded that these markers have certain diagnostic value for fetal abnormalities [ 24 ]: IFA had a certain value in the diagnosis for trisomy 21 and trisomy 18; FMA had the excellent accuracy in detecting trisomy 18; MNM angle and FS distance were reliable indicators for screening CLP, which was consistent with this study.…”
Section: Discussionsupporting
confidence: 84%
“…However, manual measurement is laborious and complex, and identifying a technique that can precisely and swiftly measure fetal facial markers is of significant clinical value. In this study, the average inference speed achieved by our model was 0.76 s per image, significantly outperforming manual measurements, which required approximately 2 min per image [ 24 ]. Our AI-based approach for measuring facial markers can accelerate the measurement process by a factor of approximately 120.…”
Section: Discussionmentioning
confidence: 99%
“…At present, studies these facial markers mainly focus on the second and third trimester, we previously demonstrated the feasibility of measuring these markers during the rst trimester, with excellent intraand inter-operator consistency. 18 We further concluded that these markers have certain diagnostic value for fetal abnormalities 20 : IFA had a certain value in the diagnosis for trisomy 21 and trisomy 18; FMA had the excellent accuracy in detecting trisomy 18; MNM angle and FS distance were reliable indicators for screening CLP, which was consistent with this study.…”
Section: Results In the Context Of What Is Knownsupporting
confidence: 75%
“…In this study, the average inference speed achieved by our model was 0.76 sec per image, signi cantly outperforming manual measurements, which required approximately 2 min per image. 20 Our AI-based approach for measuring facial markers can accelerate the measurement process by a factor of approximately 120. These ndings suggest that the AI model for measuring facial markers can facilitate manual measurements, improve work e ciency of sonographers and accelerate early clinical evaluation of fetal prognosis.…”
Section: Results In the Context Of What Is Knownmentioning
confidence: 99%